Handy Scrubby / Nor Syahdani Zulkifli … [et al.] - Zulkifli, Nor Syahdani; Zulkarnain, Nur Ayuni Kartini; Tengku Baharim, Tengku Aishah Fatimah; Ridhwan Deepak Anopchan, Putri Huda Zafirah; Wee, Hassnah (Faculty of Computer and Mathematical Sciences, 2022)
During adventures and explorations within remote areas, such as forests, mountains, and other areas devoid of laundry facilities, travellers frequently have complications with washing their clothes. Consequently, the inventive foldable bag known as the handy scrubby is designed. Handy refers to something that is convenient and simple to use, whereas scrubby refers to the act of scrubbing. The primary goal of the device is to make it simple and convenient for campers, hikers, and even frequent travelers who have trouble finding laundry services to wash their clothes. The product features include user-friendly, extremely lightweight, and simple to transport while travelling or engaging in beach activities. On top of that, the Handy Scrubby product supports the Sustainable Development Goals (SDG7), which is affordable and clean energy. This is due to the effectiveness of Handy Scrubby in promoting the functionality of a product with no electricity power needed and also affordable to purchase. Other than that, Handy Scrubby also supported the (SDG6), clean water and sanitation based on our product which encouraged the users in practicing less clean water consumption. The handy scrubby is distinctive because of its user-friendly features, eco-friendliness, and suitability for a wide range of tourist markets. This product is suitable for use in natural environments such as forest, the lake, mountains and other outdoor spaces. It has the potential to be commercialised because the price is reasonable. The invention would indeed assist the community by promoting clean energy and less clean water consumption.